Biofilm formation by Pseudomonas aeruginosa and disinfectant susceptibility of planktonic and biofilm cells - Magdalena A. Olszewska; Aleksandra M. Kocot; Aleksandra Stanowicka; Łucja Łaniewska-Trokenheim (Czech Journal of Food Sciences, 2016)
Epifluorescence microscopy (EFM) was used to study the biofilm formation of Pseudomonas aeruginosa after 6, 24, 30, 48, 54, 72, 78, and 96 h growth in a chamber slide system. For this purpose, the biofilm was stained with the Live/Dead BacLight, wherein live and dead cells were visualised based on the cell membrane integrity. With the use of EFM we described 8- of 9-stage biofilm characteristics after 78 h of growth, since the majority of microscopic fields were fully covered with attached cells. However, the 96-h growth resulted in the cell detachment and revealed 30% of dead cells of all those cells that remained on the surface. The susceptibility testing of planktonic and biofilm cells to two disinfectants, chlorine-based and quaternary ammonium compound-based, revealed that biofilm cells were more tolerant to a chlorine-based sanitiser than planktonic counterparts. P. aeruginosa was inhibited by lower concentrations of the quaternary ammonium compound-based sanitiser than the chlorine-based sanitiser, which on the other hand was more effective in cell inactivation, as both the MIC/MBC (inhibitory/bactericidal) measurement and the CFDA/PI (carboxyfluorescein diacetate/propidium iodide) staining indicated.